1997
DOI: 10.1086/517332
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Marrow Progenitors of Both Granulocytic and Monocytic Lineages Are Susceptible to Infection with the Agent of Human Granulocytic Ehrlichiosis

Abstract: Primary Bone Marrow Progenitors of Both Granulocytic and Monocytic/ primary human bone marrow cells, stimulated to differentiate along myelomonocytic lineages, were incubated with the HGE agent. Immature marrow progenitors and, remarkably, not only granulocytic but also CD14 / monocytic cells from these cultures supported replication of the HGE agent, suggesting that all are potential targets of infection in vivo. Infection of bone marrow progenitors may contribute to the hematologic manifestations of HGE. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 14 publications
(7 reference statements)
3
51
0
1
Order By: Relevance
“…The VIM-2 MAB, directed against the closely related sialylated CDw65 carbohydrate moiety, had irregular blocking activity noted only at the highest concentration tested (40 µg/ml), with a maximal reduction in infection to 60% of the level seen in untreated controls, suggesting either nonspecific effects or biologic cross-reactivity of high concentrations of VIM-2 against CD15s (22). Anti-CD15s antibody was also tested for its ability to block infection of those nontransformed cells likely to be natural targets of the HGE agent: human marrow progenitors and peripheral blood monocytes and granulocytes (5). As observed in HL60 cells, 10 µg/ml of MAB CSLEX1 prevented infection of all of these cell types (P < 0.001 vs. untreated controls).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The VIM-2 MAB, directed against the closely related sialylated CDw65 carbohydrate moiety, had irregular blocking activity noted only at the highest concentration tested (40 µg/ml), with a maximal reduction in infection to 60% of the level seen in untreated controls, suggesting either nonspecific effects or biologic cross-reactivity of high concentrations of VIM-2 against CD15s (22). Anti-CD15s antibody was also tested for its ability to block infection of those nontransformed cells likely to be natural targets of the HGE agent: human marrow progenitors and peripheral blood monocytes and granulocytes (5). As observed in HL60 cells, 10 µg/ml of MAB CSLEX1 prevented infection of all of these cell types (P < 0.001 vs. untreated controls).…”
Section: Resultsmentioning
confidence: 99%
“…This procedure killed any remaining infectious extracellular organisms (data not shown), thus enabling assessment of the effects of antibody on intracellular organisms alone. Cells were incubated as described (4,5) and assessed for infection (see later here) daily.…”
Section: Hge Infection Cultivation and Antibody Blocking Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The finding of morulae within monocytes was interesting and was similar to some human cases of HGE (Dumler SJ, unpublished data) but infrequently reported in the literature. However, Klein and others 20 reported that bone marrow monocyte progenitor cells became infected with the HGE agent in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In some assays, HL-60 cells were exposed to heat-killed HGE bacteria for 24 h or to supernatant (10 ml of supernatant from Ehrlichia-infected HL-60 cells) for 5 days. HL-60 cells (2 ϫ 10 5 /ml) were incubated at 37°C in 5% CO 2 with 1 M retinoic acid and cultured for 6 days for maximum differentiation (3,16,17). Superoxide anion was measured in both control and infected (both uninduced and retinoic acidinduced) HL-60 cells.…”
Section: Cultivation Of the Hge Agent And Superoxide Releasementioning
confidence: 99%